A Comparison between Indoor and Outdoor Rape Suspects in Sweden. Issue 5 (4th May 2022) - Khoshnood, Ardavan; Ohlsson, Henrik; Sundquist, Jan; Sundquist, Kristina
ABSTRACT: As the number of rapes is increasing in Sweden, and the number of individuals convicted of these crimes is decreasing, it is of importance to study offender characteristics of those committing these crimes and the circumstances in which these crimes are conducted, such as indoors or outdoors. Data from Swedish population-based registers were used to identify individuals suspected of rape, aggravated rape, attempted rape or attempted aggravated rape (in short: rape+) against females ≥18 years old between 2007–2017. Latent Class Analysis was then used to identify classes of rape+ suspects with respect to the location of the rape+ and then compare the two groups. A total of 19, 723 individuals were included of which the majority (n = 17, 520; 88.8%) were suspected of indoor rape+. In both groups, we identified a low offenders' class and a high offenders' class. In addition, first-generation immigrants had a higher odds of being suspected of outdoor rape+ than Swedish-born suspects, and a previous conviction of violent crime was a risk factor for committing outdoor rape+.